2019
DOI: 10.2147/dddt.s223322
|View full text |Cite
|
Sign up to set email alerts
|

<p>Catalpol Enhances Neurogenesis And Inhibits Apoptosis Of New Neurons Via BDNF, But Not The BDNF/Trkb Pathway</p>

Abstract: BackgroundThe role of catalpol in brain neurogenesis and newborn neuron survival has not been previously determined in permanent middle cerebral artery occlusion (pMCAO).MethodsFifty-four rats were divided into 6 groups: pMCAO (model, n=9); sham operation (NS, n=9); catalpol treatment (5 mg/kg and 10 mg/kg subgroups, n=9 each); K252a (n=9); and K252a+catalpol 5 mg/kg (n=9) with stroke. The effects of catalpol on behavior, neurogenesis surrounding the infarction ipsilateral to pMCAO, and the expression of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Sprague-Dawley rats were anesthetized and heparinized (0.2 mL, I.P .). Then the CA/CPR rat model was established by the previous method [ 30 ] (described in Additional file 1 ). Rats were randomized into three groups: (1) sham (n = 6), which were subjected to the same procedure as the other groups except for CA/CPR; (2) Control group (n = 6), which underwent 5 min of CA and received injection of same volume of saline; (3) DATS@MION-PEG-LF group (n = 6), which underwent 5 min of CA and received injection of DATS@MION-PEG-LF (10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Sprague-Dawley rats were anesthetized and heparinized (0.2 mL, I.P .). Then the CA/CPR rat model was established by the previous method [ 30 ] (described in Additional file 1 ). Rats were randomized into three groups: (1) sham (n = 6), which were subjected to the same procedure as the other groups except for CA/CPR; (2) Control group (n = 6), which underwent 5 min of CA and received injection of same volume of saline; (3) DATS@MION-PEG-LF group (n = 6), which underwent 5 min of CA and received injection of DATS@MION-PEG-LF (10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…42 In addition, it has been reported that Catalpol increases neurogenesis and inhibited apoptosis of new neurons by promoting BDNF expression. 43 Interestingly, BDNF also plays an important role in adult neurogenesis. 44 Ki-67 and NeuN, important markers of neurogenesis, are essential for specific functions in the mammalian hippocampus, presumably related to cognitive function.…”
Section: Chronic Exposure To Pb Mostly By Inhalation and Ingestion Increasesmentioning
confidence: 99%
“…This is likely due to the activation of SIRT1 expression by resveratrol, which enhances neurogenesis and inhibits apoptosis of nascent neurons by promoting BDNF. 43,49 However, the hypothesis that CREB/BDNF enhances neurogenesis should be interpreted with caution. This presumption will be further verified by cell culture experiments.…”
Section: Chronic Exposure To Pb Mostly By Inhalation and Ingestion Increasesmentioning
confidence: 99%
“…Catalpol is one of the main chemical extracts of RG. It protects dopaminergic neurons from damage in PD, 116 enhances neurogenesis and inhibits apoptosis of new neurons by activating BDNF, 117 ameliorates hyperactive and impulsive behavior, improves spatial learning and memory, 118 improves axonal growth by regulating miR-124 after ischemia, 119 relieves neuralgia, 120 and has antidepressant effects. 121 Cinnamomum cassia (L.) J. Presl CS is in the family of camphor, it is a medium-sized tree of the camphor family, and its bark is gray-brown.…”
Section: Rehmannia Glutinosa (Gaertn) DCmentioning
confidence: 99%